Ultrastructural response of the retinal cells and neurovascular unit to neuroinflammation induced by lipopolysaccharide - Bilin Rao; Xiaotian Wu; Xiaoqing Liu; Fenglan Wang; Fang He; Xin Lin; Guiyu Guan; Xiaoqian Lai; Jun Zhang (Brain Structure and Function, 2026)

Sex differences in resting-state hypothalamic connectivity and its relationship with negative emotion and behavior measures in young adults - Guangfei Li; Yiran Shao; Lin Yang; Yanan Su; Mengmeng Wang; Zhao Zhang; Xiaoyi Sun; Bao Li; Xiaolin Wang; Yu Chen; Guangyu Bin; Chiang-Shan R. Li (Brain Structure and Function, 2026)

Distinct cellular localization of α- synuclein and β-synuclein in the chick retina - Fang He; Lin Liu; Shaoxuan Wang; Xin Lin; Guiyu Guan; Xiaoqian Lai; Xi Yu; Xiaotian Wu; Zhihao Shen; Bilin Rao; Mei-Ling Gao; Xuejiao Chen; et al. (Brain Structure and Function, 2025)

Beyond tractography in brain connectivity mapping with dMRI morphometry and functional networks - Jui-To Wang; Ching-Po Lin; Huei-Min Liu; Carlo Pierpaoli; Chun-Yi Zac Lo (Brain Structure and Function, 2025)
Traditional brain connectivity studies have focused mainly on structural connectivity, often relying on tractography with diffusion MRI (dMRI) to reconstruct white matter pathways. In parallel, studies of functional connectivity have examined correlations in brain activity using fMRI. However, emerging methodologies are advancing our understanding of brain networks. Here we explore advanced connectivity approaches beyond conventional tractography, focusing on dMRI morphometry and the integration of structural and functional connectivity analysis. dMRI morphometry enables quantitative assessment of white matter pathway volumes through statistical comparison with normative populations, while functional connectivity reveals network organization that is not restricted to direct anatomical connections. More recently, approaches that combine diffusion tensor imaging (DTI) with functional correlation tensor (FCT) analysis have been introduced, and these complementary methods provide new perspectives into brain structure–function relationships. Together, such approaches have important implications for neurodevelopmental and neurological disorders as well as brain plasticity. The integration of these methods with artificial intelligence techniques have the potential to support both basic neuroscience research and clinical applications.

Developmental expression of α- and β- synuclein in the mouse retina - Wenhui Zhong; Zhongqun Chen; Shaoxuan Wang; Jun Cao; Xin Lin; Xiaoqian Lai; Bilin Rao; Jun Zhang (Brain Structure and Function, 2025)

Classifying athletes and non-athletes by differences in spontaneous brain activity: a machine learning and fMRI study - Lei Peng; Lin Xu; Zheyuan Zhang; Zexuan Wang; Xiao Zhong; Letong Wang; Ziyi Peng; Ruiping Xu; Yongcong Shao (Brain Structure and Function, 2025)

Decreases in frequency-dependent intrinsic activity of the default mode network are associated with depression and cognition in patients with postacute sequelae of SARS-CoV-2 infection - Yao Wang; Ziwei Yang; Xiumei Zheng; Xiao Liang; Lin Wu; Chengsi Wu; Jiankun Dai; Yuan Cao; Xianjun Zeng; Meng Li; Fuqing Zhou (Brain Structure and Function, 2025)

Cell-specific localization of β-synuclein in the mouse retina - Wenhui Zhong; Qingwen Yang; Fenglan Wang; Xin Lin; Zhongqun Chen; Jing Xue; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Jun Zhang (Brain Structure and Function, 2024)

Distribution and synaptic organization of substance P-like immunoreactive neurons in the mouse retina - Fenglan Wang; Wenhui Zhong; Qingwen Yang; Wenna Zhao; Xiaoqing Liu; Bilin Rao; Xin Lin; Jun Zhang (Brain Structure and Function, 2023)

Diffeomorphic registration for retinotopic maps of multiple visual regions - Yanshuai Tu; Xin Li; Zhong-Lin Lu; Yalin Wang (Brain Structure and Function, 2022)

The impact of Alzheimer's disease susceptibility loci on lateral ventricular surface morphology in older adults - Shan Li; Na An; Nan Chen; Yin Wang; Lin Yang; Yalin Wang; Zhijun Yao; Bin Hu (Brain Structure and Function, 2022)

Postnatal development of BAG3 expression in mouse cerebral cortex and hippocampus - Xinlu Li; Geng Lin; Tongtong Liu; Ning Zhao; He Xu; Huaqin Wang; Wei Zheng (Brain Structure and Function, 2021)

Dissociable plasticity of visual-motor system in functional specialization and flexibility in expert table tennis players - Dazhi Yin; Xuefei Wang; Xiaoyou Zhang; Qiurong Yu; Yu Wei; Qing Cai; Mingxia Fan; Lin Li (Brain Structure and Function, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

Dissociating the neural correlates of the sociality and plausibility effects in simple conceptual combination - Nan Lin; Yangwen Xu; Huichao Yang; Guangyao Zhang; Meimei Zhang; Shaonan Wang; Huimin Hua; Xingshan Li (Brain Structure and Function, 2020)

Cortical thickness and surface area in neonates at high risk for schizophrenia - Gang Li; Li Wang; Feng Shi; Amanda E. Lyall; Mihye Ahn; Ziwen Peng; Hongtu Zhu; Weili Lin; John H. Gilmore; Dinggang Shen (Brain Structure and Function, 2016)

Dorsal hippocampal brain receptor complexes linked to the protein synthesis-dependent late phase (LTP) in the rat - Lin Li; Han Wang; Maryam Ghafari; Gunyong An; Volker Korz; Gert Lubec (Brain Structure and Function, 2015)

Orexins (hypocretins) contribute to fear and avoidance in rats exposed to a single episode of footshocks - Xiaoyu Chen; Huiying Wang; Zhang Lin; Sa Li; Yonghui Li; Hugo T. Bergen; Maria E. Vrontakis; Gilbert J. Kirouac (Brain Structure and Function, 2014)

Medullo-ponto-cerebellar white matter degeneration altered brain network organization and cortical morphology in multiple system atrophy - Chia-Feng Lu; Po-Shan Wang; Yuan-Lin Lao; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Brain Structure and Function, 2014)

Differential distribution and activation of microglia in the brain of male C57BL/6J mice - Ting-Ting Yang; Chingju Lin; Chao-Tien Hsu; Tzu-Feng Wang; Fang-Yi Ke; Yu-Min Kuo (Brain Structure and Function, 2013)